Efficient identification of hydrophobic MOFs: application in the capture of toxic industrial chemicals. Issue 2 (9th December 2015) - Moghadam, Peyman Z.; Fairen-Jimenez, David; Snurr, Randall Q.
Abstract : A novel and quick computational strategy is developed based on water Henry's constants to distinguish different levels of hydrophobicity among metal–organic frameworks. The technique is applied to a large database of MOFs to identify hydrophobic materials. Abstract : Water is an ever-present component in the air, and competitive adsorption of water is a major challenge in many applications of adsorbents, including capture of toxic industrial chemicals (TICs) from the atmosphere. For metal–organic framework (MOF) adsorbents, the presence of water often leads to major material instabilities that could limit their practical performance. MOFs displaying hydrophobic behavior might be useful in overcoming these problems. In this work, we present a new computational strategy to quickly identify hydrophobic MOFs based on their water Henry's constants. Starting with a database of 137 953 hypothetical MOFs, we identified 45 975 structures as hydrophobic based on their simulated water Henry's constants. Using grand canonical Monte Carlo simulations, we further analyzed 2777 of these hydrophobic materials whose linkers did not contain chemical functionalization. The results show insignificant water uptake in the identified MOFs, confirming their hydrophobic nature. The capability of the hydrophobic MOFs was assessed for ammonia capture under humid conditions, and analysis of the data generated from this high-throughput computational screening revealed the role of the textural properties and surface chemistry on the removal of toxic compounds. The results suggest that if materials are too hydrophilic, they adsorb too much water and show little or no selectivity towards TICs. On the other hand, if they are too hydrophobic, they adsorb too little ammonia.